Electrical promotion of spatially photoinduced charge separation via interfacial-built-in quasi-alloying effect in hierarchical Zn2In2S5/Ti3C2(O, OH)x hybrids toward efficient photocatalytic hydrogen evolution and environmental remediation - Wang, Hou (2021)
Exploring new hybridized catalysts for synergistically promoting the photocatalytic efficiency hold great challenges in solar-to-chemical energy conversion and environmental remediation. Hierarchical Zn2In2S5/Ti3C2(O, OH)x hybrids have been rationally constructed using Ti3C2(O, OH)x as a two-dimensional platform for in situ growth of flower-like Zn2In2S5 microsphere under anaerobically hydrothermal conditions. Upon exposure to visible light, the Zn2In2S5/Ti3C2(O, OH)x hybrids with the Ti3C2(O, OH)x content of 1.5% (by mass) had hydrogen generation yields of 12,983.8 μmol g−1, which was significantly better than that of pure Zn2In2S5. The apparent quantum efficiency reached 8.96% at 420 nm. Furthermore, the photocatalytic tetracycline removal rate was ˜1.25 times higher than that of pure Zn2In2S5, and can be further improved with the increase of temperature in the range of 35–55 °C. Excellent photocatalytic activity originated from the synergistic effects between visible-light-active Zn2In2S5 and conductive Ti3C2(O, OH)x for spatial electrical promotion. The photogenerated-electrons transfer efficiency from Zn2In2S5 to Ti3C2(O, OH)x was 33.0%. In accordance with spectroscopic, electrochemical, and density functional theory studies, we proposed that the interfacial-built-in quasi-alloying effect between ZIS and Ti3C2(O, OH)x culminated in notable charge redistribution, which thereby facilitated the spatial separation and transfer of photogenerated electron-hole pairs. This work revealed the underlying photo-excited charge transfer between metallic compound and semiconductor.